Spanish Validation of the Multidimensional Existential Meaning Scale: Which Dimension of Meaning in Life Is More Associated With Psychopathology in People With Mental Disorders? - Marco, Jose Heliodoro; García-Alandete, Joaquín; Pérez Rodríguez, Sandra; Guillén, Verónica; Baños, Rosa M.; Tormo-Irun, Maria Pilar (Frontiers in Psychiatry, 2022)
To assess three dimensions of Meaning in Life (comprehension, purpose, and mattering) the Multidimensional Existential Meaning Scale (MEMS) was developed, however, the MEMS `s factorial structure has not yet been confirmed in a Spanish-speaking sample. A question that remains unanswered is which of the three dimensions of MiL are associated with psychopathology in clinical samples. Objective: (1) to analyze the psychometric properties of the MEMS in a Spanish non-clinical population, and (2) to identify which of the three dimensions of MiL shows the strongest relationship with depression, anxiety and positive affect in a clinical population. Method: The non-clinical sample, consisted of N = 683 Spanish adults, and the clinical sample consisted of 88 adults diagnosed with mental disorders. A Confirmatory Factor Analysis and regression analysis were carried out. Results: The three-factor model for the MEMS showed an acceptable fit, and full invariance across gender groups. In the clinical sample, the mattering dimension had the highest association with depression and anxiety, and purpose with positive affect. Conclusions: The MEMS is an adequate instrument to assess the three dimensions of meaning in Spanish-speaking participants. These results support the importance of evaluating the MiL construct from a multidimensional perspective in clinical samples.